FAKTOR RISIKO LINGKUNGAN GIZI KURANG DAN GIZI BURUK PADA BALITA 12-59 BULAN - Alamsyah, Dedi (JURNAL BORNEO AKCAYA, 2015)
Background, Moderate and severe malnutrition in Pontianak each years trend of decreasing prevalence of cases malnutrition , but case numbers are still above 10 % . Non Problem Based Health according to WHO , the prevalence of the area is less weight above 10.0 % , while malnutrition has increased well as the decline is not drastic cases of less nutrition . The prevalence of malnutrition and malnutrition in 2011 by weight for age amounted to 18.94 % and 1.94 %, in 2012 10.91 % and 2.75 % , while in 2013 amounted to 10.60 % and 2,47 % . The purpose of this study prove the environmental risk factors that affect the incidence of moderate and malnutrition among children under five years old aged 12-59 months. Method: The type of research was observational using the quantitative study design of case control study. Results, The bivariate analysis found five (5) variables significantly associated with the prevalance of moderate and severe malnutrition in children under five years old aged 12-59 months, i.e.: low maternal education (OR: 7.07 p = 0.001 95% CI 2.06 - 16.079), poor of attitude toward food (OR: 5.76 p = 0.001 95% CI 2.51 - 19.85), poor environmental sanitation (OR: 4.33 p = 0.004 95% CI -11.06 - 1.69), low family income (OR: 4.20 p = 0.020 95% CI 1.35 - 13.06) and low family income and a larger number of children two (OR : 0,040 p = 0,040 95 % CI 1,14-7,39).